The association of coagulation and hemostasis with atrial fibrillation: a systematic review and meta-analysis. (11th May 2022) - Tilly, MJ; Geurts, S; Pezzullo, AM; Bramer, WM; Ikram, MA; De Groot, NMS; Kavousi, M; De Maat, MPM
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): - Erasmus MC MRace grant- The Netherlands Organization for the Health Research and Development (ZonMw) Background: Atrial fibrillation (AF) is a highly prevalent cardiac tachyarrhythmia. Recent literature suggests that AF induces a prothrombotic state, ultimately leading to thrombotic events. It is also hypothesized that coagulation underlies AF development through coagulation. Purpose: We aimed to assess the associations between selected coagulation factors with AF in both longitudinal and cross-sectional studies, to give further insight on the interaction of coagulation and AF. Methods: Through a systematic search of large databases, including Embase, Medline ALL, and Web of Science Core Collection, all longitudinal cohort studies and cross-sectional studies published before 25th of May, 2021 were reviewed. For longitudinal studies, pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated through log-transformed HRs and 95% CIs using the generic inverse variance method. For cross-sectional studies the pooled standardized mean differences (SMD) were calculated through inverse variance weighting. Results: 16 longitudinal studies and 44 cross-sectional studies were included. In the longitudinal studies, using complex multivariable models, we found significant associations between fibrinogen (HR1.06, 95% CI 1.01-1.12), Plasminogen activator inhibitor 1 (PAI-1) (HR 1.06, 95% CI 1.00-1.12), and D-dimer (HR 1.10, 95% CI 1.02-1.19), with AF incidence. In cross-sectional studies, we found significant differences between AF patients and controls for fibrinogen (SMD 0.47), D-dimer (SMD 1.74), P-selectin (SMD 0.31), von Willebrand factor (SMD 0.96), PAI-1 (SMD 1.73), ß-thromboglobulin (SMD 0.82), and Platelet Factor 4 (SMD 0.42). Conclusions: Atrial fibrillation is associated with higher levels of coagulation factors. These associations are most pronounced in cross-sectional analyses, but limited studies are available investigating a prothrombotic state underlying AF initiation. These results further support the hypothesis of "AF begets AF".